Analisis Silistika Pada Puisi “Kau Ini Bagaimana Atau Aku Harus Bagaimana” Karya Gus Mus - Asep Maulana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
Literary work is a study of stylistics that uses literary language styles as a medium to discover its aesthetic value. Stylistics is the science of using language in literary works. The use of specific language styles in literary works created by the author himself. Therefore, the objective of this research analysis aims to determine the use of language styles (figure of speech), describe the diction and message to be conveyed in the poem "How are you or what should I do" by KH Mustofa Bisri. Based on the stylistic approach put forward as the basis for the theoretical study used in the analysis. This type of research uses qualitative methods. The theory used is stylistic theory with a stylistic approach. This is able to convey messages indirectly to the reader, what attitudes and behavior should be carried out. Based on the results of the analysis of the poem You Are How or I Have to How by KH Mustofa Bisri which highlights various aspects of strong and unexpected word formation in order to find out about the implied meaning that KH Mustofa Bisri wants to convey through the application of language styles (figure of speech), so that the meaning is hidden in The poem "How are you or what should I do" can be clearly expressed by the author. The author found the language styles of association, irony, parallelism and paradox, there are 6 language styles (figure of speech) which are divided into; 1 association, 2 ironies, 2 parallelisms and 1 paradox. Based on the results of the analysis, from the poem "How are you or what should I do" by Gus Mus, 6 language styles were obtained.